Design and Characteristics of a Wireless Non-enzyme Glucose Sensor Based on Resonant LC Passive Circuit - Thanh, Pham Van; Phu, Nguyen Van; Anh, Bui Van (VNU Journal of Science: Mathematics - Physics; Vol 40 No 4, 2024)
In this work we present a development of a reusable wireless non-enzyme glucose sensor based on the resonant inductor-capacitor (LC) passive circuit fabricated explicitly on a low-cost FR4 substrate. In our experiments, glucose/water solutions with varying concentrations have been utilized to evaluate the characteristics of the proposed structure. The obtained results showed that the fabricated sensor’s effectiveness in accurately identifying glucose concentrations ranging from 0.1 mM to 100 mM. The sensor’s sensitivities were estimated to be 9.595 MHz/mM, 0.7659 MHz/mM, and 0.2709 MHz/mM for 0.1 to 0.9 mM, 1 to 10 mM, and 10 to 100 mM glucose concentration ranges, respectively. The sensor’s limit of detection (LOD) was calculated to be 0.105 mM for the glucose range from 0.1 to 0.9 mM. In particular, the sensitivity changes most significantly within the glucose concentration range of 0.1 to 0.9 mM, indicating that the sensor is particularly effective at detecting lower glucose concentrations. The obtained characteristics suggest that this sensor is suitable for applications requiring precise measurements of glucose solution.